THE IMPACT OF ARTIFICIAL INTELLIGENCE ON SEARCH ENGINE OPTIMIZATION STRATEGIES - Aldo Faisal Umam (International Conference on Economic Business and Social Science, 2023)
This study examines the impact of artificial intelligence (AI) on search engine optimization (SEO) strategies. In recent years, search engines have undergone significant changes in the use of AI technology to improve the quality of search results. Although the implementation of AI technology in SEO is still relatively new, research has shown that the use of this technology can help improve the quality of search results and provide a better search experience for users. This article discusses how AI technology can help improve the quality of search results through content optimization, the development of more sophisticated search algorithms, and the use of machine learning and natural language processing techniques to understand the search context and provide more relevant results. In addition, this article also discusses the implications of using AI technology in SEO and the challenges that may be faced in implementing this technology. In this study, the research method used is a literature review, by collecting and analyzing data from academic sources and related publications. By examining the literature, this study highlights the potential benefits and limitations of using AI technology in SEO, and provides insights into the future direction of search engine optimization strategies. Overall, this article contributes to the growing body of knowledge on the role of AI technology in improving search engine optimization strategies, and provides valuable insights for researchers, practitioners, and industry professionals in this field.